OPPORTUNITY FOR INCREASING THE PRODUCTION OF RUMINANTS, SUCH AS CATTLE, BUFFALOES, SHEEP AND GOATS IN THE FOOT-HILL AND MOUNTAIN REGIONS OF BULGARIA - Tsvetan MARKOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper investigates the current state of production from cattle, buffaloes, sheep and goats in the hilly, foot-hilly and mountain regions of Bulgaria, as well as the opportunities for its increase. Negative trend were observed in the populations of cattle, sheep and goats in the last two decades. 634,466 cattle were raised in Bulgaria in 2001, 371,901 of which were dairy cows. Data for 2020 showed values of 568,700 heads of cattle, 365,500 of which were dairy cows and pregnant heifers. In this period, the number of sheep decreased from 1,571,410 in 2001 to 1,307,800 in 2020, and the decline in goats was even more noticeable, from 675,292 in 2001 to 253,400 in 2020. The decline in the breeding of farm animals led to a decrease in the volume of animal milk and meat products. For the positive development of the volume of agricultural production in the foot-hilly and mountain regions of Bulgaria, decisions are needed to improve the gene pool, health care, feeding, as well as the application of advanced modern technologies. The advantage of mountain and foot-hilly agriculture is in the creation of high-quality food products and for this reason it is necessary to support it through appropriate measures and programs.